Surveyor training for housing backlog data collection using location intelligence technology in Krendang Village, West Jakarta - Wahyu Sejati; Agung Sediyono; Arief Fadhilah; Ryan Faza Prasetyo (Community Empowerment, 2022)
One of the problems of population density is the lack of adequate housing. Krendang Village is one of the most densely populated urban areas with a population density of 76,124 inhabitants/km2. Surveyor training is needed to provide understanding and knowledge to avoid errors in housing backlog data collection during field surveys. The housing backlog data collection process is carried out using the data collection method directly to residents' homes using the MAPID form to facilitate filling out questionnaires based on location intelligence technology. The results of this housing backlog survey can be used as a policy basis for structuring slum areas and also identifying the demographic map of the Krendang Village area. This surveyor training also produces a housing backlog module that can be used as a reference for surveyors.